APPROACHES TO INCREASE THE AVAILABILITY AND EFFECTIVENESS OF PRE-HOSPITAL THROMBOLYSIS IN REAL CLINICAL PRACTICE - L. A. Ostroumova; S. V. Shalaev (Рациональная фармакотерапия в кардиологии)
Aim. To identify the factors of the increasing the availability and effectiveness of pre-hospital thrombolytic therapy of patients with ST segment elevation acute coronary syndrome (STEACS). Material and methods. STEACS patients (n=70) were included in the study and stratified into two groups. Patients of the 1st group (n=30) received emergency medical assistance from the feldsher teams and patients of the 2nd group (n=40) — from the doctor teams. Expert estimation approach was used for the real practice assessment. Results. The hospital-matched diagnose rate was 97.5% in the doctor teams in comparison with 76.7% in feldsher teams (p<0.05). The efficiency of pre-hospital thrombolysis in 90 minutes after its beginning was 60.1% for the doctor teams versus 73.3% for the feldsher teams (p>0.05). The deviation from the standard operating procedure of the medical care for myocardial infarction patients was observed more often in the doctor teams in comparison with this in the feldsher teams. Time for the decision about pre-hospital thrombolysis start, the rate of unreasonable use or unreasonable refusal of thrombolysis did not differ significantly in feldsher and doctor teams. Conclusion. To increase the effectiveness of pre-hospital thrombolysis therapy it is necessary to follow strictly the standard of the medical care for patients with acute coronary syndrome. One of the main approaches to improve the availability of up to date medical care technologies in STEACS treatment is implementation of pre-hospital thrombolysis in practice of feldsher teams.